An econometric analysis of the economic and environmental efficiency of dairy farms in the KwaZulu-Natal Midlands - Mkhabela, Thulasizwe (Stellenbosch : University of Stellenbosch, 2011)
Thesis (PhD(Agric) (Agricultural Economics))--University of Stellenbosch, 2011.